Editorial to JHIA Vol. 5 (2018) Issue 1 - Mostert, Nicky (Journal of Health Informatics in Africa, 2018)
The Journal of Health Informatics in Africa is the official journal of the Pan African Health Informatics Association (HELINA). Whilst JHIA publishes the proceedings of the HELINA conferences, this issue consists of three papers that were submitted directly to the journal and is thus an open-call issue. The next issue that will be published before the end of 2018 will consist of the papers that were accepted for the HELINA 2018 conference that was held in Kenia at the beginning of December 2018. All papers in both open-call, as well as conference issues, are double blind peer reviewed before being accepted for publication. Although JHIA also publishes papers written in French, all three papers in this issue were written in English. A framework for the management of diabetes in the Mauritian context is proposed and the effectiveness of ICT interventions for diabetes are also investigated. The causes for Sub-Saharan Africa’s lag in Electronic Health Record (EHR) adoption is also explored, and possible strategies to increase (EHR) adoption in this region proposed. Thank you to the editorial team, authors, and peer reviewers that made this issue possible.